2012
DOI: 10.1021/ct3001969
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Anisotropic Shape and Electrostatic Models for Biological Bromine Halogen Bonds

Abstract: Halogens are important substituents of many drugs and secondary metabolites, but the structural and thermodynamic properties of their interactions are not properly treated by current molecular modeling and docking methods that assign simple isotropic point charges to atoms. Halogen bonds, for example, are becoming widely recognized as important for conferring specificity in protein-ligand complexes but, to this point, are most accurately described quantum mechanically. Thus, there is a need to develop methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
130
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(131 citation statements)
references
References 51 publications
1
130
0
Order By: Relevance
“…We have approached the problem of modeling BXBs from a different perspective, by deriving an empirical force field for BXBs 11 that, unlike the pseudo-atom approach, is based on the fundamental atomic properties of size, shape, and electrostatic charge (Fig. 3b).…”
Section: Introductionmentioning
confidence: 99%
“…We have approached the problem of modeling BXBs from a different perspective, by deriving an empirical force field for BXBs 11 that, unlike the pseudo-atom approach, is based on the fundamental atomic properties of size, shape, and electrostatic charge (Fig. 3b).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast P. Shing Ho and colleagues have created a force field (ffBXB) that provides an anisotropic treatment of both the shape and electrostatic charge parameters of bromine. 21 They have suggested that electrostatics alone cannot account for the very short-range distances of bromine halogen bonds but require a flattening of the effective van der Waals radius. This approach was recently also extended to chlorine and iodine 22 .…”
Section: From Qm To Scoring Functionsmentioning
confidence: 99%
“…Scoring and visualization of halogen bonds toward the backbone carbonyl will also be made available via a web interface at www.halogenbonding.com. 21 …”
mentioning
confidence: 99%
“…Although the function performs well in certain cases, it is still a challenge to parametrize properly the location and the charge of the extra dummy atoms owing to the complexity of the halogenated moieties and the diversity of the possible dummy atom construction schemes [46]. Megan Carter and coworkers developed a set of force-field based potential functions, without using extra dummy atoms, to model the anisotropic structure-energy relationships for bromine halogen bonding [50]. However, to the best of our knowledge, the scoring functions, which can both describe appropriately halogen bonding and are suitable for high-throughput virtual screening at the same time, are highly insufficient.…”
Section: Introductionmentioning
confidence: 99%